Electrical Characterization of Commercial Power MOSFET Under Electron Radiation - Wan Nurhasana binti Wan Ayub; Nurul Fadzlin Hasbullah; Abdul Wafi Rashid (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper presents the threshold voltage shifts for both p-channel and n-channel commercial power MOSFET before and after electron irradiation. The experiment was done under the 3MeV energy of electron with dose level varies from 50KGy until 250KGy. The results were plotted and analyzed in terms of the shifted voltage characteristics. It is observed that after irradiation, both p-channel and n-channel MOSFET experiences negative threshold voltage shifts. For n-channel devices, this is due to the radiation-induced positive charges dominated in the oxide traps while for p-channel devices it is believed due to radiation-induced ionization damage.